Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 1 - Limits and Their Properties - Review Exercises: 76



Work Step by Step

$\lim\limits_{x\to-1^-}\dfrac{x+1}{x^4-1}=\lim\limits_{x\to-1^-}\dfrac{x+1}{(x^2-1)(x^2+1)}$ $=\lim\limits_{x\to-1^-}\dfrac{(x+1)}{(x+1)(x-1)(x^2+1)}=\lim\limits_{x\to-1^-}\dfrac{1}{(x-1)(x^2+1)}$ $=\dfrac{1}{((-1^-)-1)((-1^-)^2+1)}=-\dfrac{1}{4}.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.